Impact of root observation windows on plant performance, root development, and rhizosphere-microbial communities during late vegetative growth of field-grown winter wheat - Loreen Sommermann; Jan Helge Behr; Narges Moradtalab; Saskia Windisch; Soumitra Paul Chowdhury; Michael Rothballer; Ingo Schellenberg; Doreen Babin; Kornelia Smalla; Lorrie Maccario; SØren J. SØrensen; Uwe Ludewig; et al. (Plant and Soil, 2026)
Background and Aims Root observation windows (RW) installed in the field provide a tool for non-destructive monitoring of root development and rhizosphere processes. However, the highly invasive installation process, which requires cutting soil profiles, may affect plant development and, ultimately, the outcome of the experiments. This study systematically compares plant development with and without the installation of RW. Methods Using the location of a long-term field experiment, the responses of winter wheat to different intensities of tillage, N-fertilization, and use of fungicides were compared for plants grown along root windows and in undisturbed control plots. Sampling was performed during late vegetative growth, six weeks after RW installation, with comparisons of shoot and root biomass, root length, mineral nutritional status, stress-related gene expression, stress metabolites, and the composition of microbial communities reflecting rhizosphere (RH) conditions. Results The presence of RW did not significantly affect most of the parameters analyzed. As an exception, RW plants showed increased foliar concentrations of several nutrients (K, Mg, Ca, Cu, Mn), potentially attributable to reduced inter-plant competition because RW were installed along border rows of the experimental plots. By contrast, N-fertilization intensity and fungicide use affected plant biomass, root growth, and fungal communities. Tillage intensity primarily affected fine-root production, the composition of RH-microbial communities, and physiological stress indicators in leaf tissue. Conclusion The results suggest only a limited influence on performance of winter wheat six weeks after RW installation under the selected experimental conditions, with plant responses and experimental results comparable to undisturbed controls.

Prokinetic drugs that stimulate 5-HT4-serotonin receptors in the human atrium - Joachim Neumann; Uwe Kirchhefer; Britt Hofmann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Several gastrointestinal drugs like bromopride, cinitapride, cisapride, clebopride, felcisetrag, metoclopramide, mosapride, naronapride, prucalopride, renzapride, tegaserod, velusetrag, and zacopride are probably agonists at 5-HT 4 -serotonin receptors in the intestine. Some of these drugs do not act selectively only on 5-HT 4 -serotonin receptors. Instead, most of them also stimulate or inhibit other serotonin receptors. In addition, they sometimes stimulate or inhibit a wide variety of additional targets such as histamine receptors, adrenoceptors, dopamine receptors, monoamine transporters, or potassium channels. We review here to which extent these drugs are potent and/or effective agonists or antagonists at human cardiac 5-HT 4 -serotonin receptors. We address the possibility that at therapeutic concentrations some of these drugs may induce cardiac side effects via 5-HT 4 -serotonin receptors. Plasma concentrations of these drugs can sometimes be elevated by drug/drug interactions such that cardiac side effects become more likely. Moreover, we address the question whether such effects occur at the human cardiac atrium or at the human ventricle. We will focus on inotropic effects, but for completeness also address potential effects on the sinus node. We will present our view where there are remaining pre-clinical or clinical research needs. One may repurpose some of these drugs to act on cardiac 5-HT 4 -serotonin receptors and discuss for which indications this may offer additional benefits.

Contractile effects of dulaglutide in the human atrium - Joachim Neumann; Milena Jarikova; Britt Hofmann; Uwe Kirchhefer; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Dulaglutide is a glucagon-like peptide 1 receptor (GLP-1R) agonist. Dulaglutide (LY2189265) is a GLP-1(7–37) analogue fused by a linker to a modified immunoglobulin G. GLP-1R agonists like dulaglutide can be used to treat diabetes type 2 and obesity. We tested the hypothesis that dulaglutide directly increased force of contraction in the human heart via GLP-1R. To this end, we conducted contraction experiments in paced (1 Hz) isolated human right atrial muscle preparations (HAP). HAP were obtained during open-heart surgery from adult patients with severe coronary heart disease. We detected a concentration- and time-dependent positive inotropic effect of dulaglutide in HAP. Dulaglutide augmented the rate of tension development, the rate of tension relaxation and accelerated the relaxation time in HAP. Dulaglutide (100 nM) augmented the phosphorylation state of phospholamban at serine 16 and the phosphorylation state of the inhibitory subunit of troponin. The positive inotropic effect of 100 nM dulaglutide in HAP was attenuated by 100 nM exendin (9–39). In contrast, dulaglutide alone or in the presence of phosphodiesterase inhibitor rolipram up to 100 nM failed to exert a positive inotropic effect in isolated electrically paced (1 Hz) mouse left atrial preparations and did not increase the beating rate of spontaneously beating mouse right atrial preparations. Our data suggest that dulaglutide raised force of contraction in the isolated paced human atrium via GLP-1R involving cAMP-dependent protein kinase in HAP.

Obituary for Prof. “Willi” Schmitz - Joachim Neumann; Uwe Kirchhefer; Frank Ulrich Müller (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Mirtazapine is a functional antagonist at cardiac human H1-histamine receptors - Thanh Hoai Pham; Jonas M. A. Schlicht; Britt Hofmann; Uwe Kirchhefer; Joachim Neumann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Mirtazapine is an atypical tetracyclic antidepressant drug that binds to several monoamine neurotransmitter receptors. For instance, mirtazapine binds to H 1 -histamine receptors in vitro and in the brain of patients in vivo. Here, we hypothesize that mirtazapine is an antagonist at human cardiac H 1 -histamine receptors. To test this hypothesis, we measured force of contraction in isolated electrically stimulated (1 Hz) left atrial preparations (LA) and spontaneously beating right atrial preparations (RA) from adult transgenic mice with cardiomyocyte-specific overexpression of the human H 1 -histamine receptor (H 1 -TG). These findings were compared with those in wild-type littermate mice (WT). Finally, we measured the force of contraction in isolated electrically stimulated right atrial muscle strips (HAP) gotten from adult patients who were undergoing bypass surgery. Mirtazapine concentration- and time-dependently decreased H 1 -histamine receptor-stimulated force of contraction in LA and RA from H 1 -TG. Importantly, mirtazapine (starting at 100 nM) concentration- and time-dependently decreased H 1 -histamine receptor-stimulated force of contraction in HAP. We thus conclude that mirtazapine can antagonize human cardiac H 1 -histamine receptors at therapeutic drug concentrations, and thus, mirtazapine may have cardiac untoward effects in psychiatric patients.

Felcisetrag stimulates 5-HT4-serotonin receptors in the human atrium - Lina Maria Rayo Abella; Joachim Neumann; Britt Hofmann; Uwe Kirchhefer; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Felcisetrag (methyl 4-[[4-[[(2-propan-2-yl-1 H -benzimidazole-4-carbonyl)-amino]-methyl]-piperidin-1-yl]methyl]piperidine-1-carboxylate, TD-8954, TAK-954) has a structural formula with similarity to serotonin. It is one of the most potent compounds to bind to recombinant human 5-HT 4 -serotonin receptors. We noted that felcisetrag raised force of contraction in left atrial preparations (LA) and beating rate in right atrial preparations (RA) from mice with cardiac-specific overexpression of the human 5-HT 4 receptors (5-HT 4 -TG) but was inactive in LA and RA from adult wild type mouse hearts (WT). When felcisetrag had increased force of contraction in LA or beating rate in RA of 5-HT 4 -TG, GR125487, a 5-HT 4 receptor antagonist, reduced force of contraction and beating rate. Felcisetrag raised force of contraction only in the presence of cilostamide in human right atrial preparations (HAP) obtained from adult patients during open heart surgery due to severe coronary heart disease. These positive inotropic effects of felcisetrag in HAP were attenuated by 1 µM GR125487. In the presence of cilostamide, 100 nM felcisetrag exerted positive inotropic effects that were increased further by 1 µM serotonin. When 1 µM serotonin had raised force of contraction, additionally applied 100 nM felcisetrag reduced force of contraction in HAP. These data suggest that felcisetrag can act as an agonist as well as an antagonist at human 5-HT 4 receptors in the mammalian heart.

Cantharidin attenuates the anti-β-adrenergic or anti-histaminergic or anti-serotoninergic effect of A1-adenosine receptor stimulation in the isolated human atrium - Rebecca Schwarz; Britt Hofmann; Uwe Kirchhefer; Joachim Neumann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
(R)-N 6 -Phenylisopropyladenosine (R-PIA), an agonist at A 1 -adenosine receptors, per se leads to so-called “direct” negative inotropic effects (NIE) in mammalian atrium. These NIE in mammalian atrium are often accentuated in the presence of cAMP-increasing agonists acting through GTP-binding stimulatory proteins in the sarcolemma such as isoprenaline (via β-adrenoceptors), histamine (via H 2 -histamine receptors) or serotonin (via 5-HT 4 -serotonin receptors) so-called “indirect” effects. Cantharidin inhibits protein phosphatases 1 and 2A (PP1, PP2A). We hypothesized that cantharidin would attenuate this NIE of R-PIA because R-PIA activated the PPs, whereas isoprenaline, serotonin, and histamine most likely inhibit PPs. Thence, during open-heart surgery in patients suffering from severe coronary heart disease, trabeculae carneae from human right atrium (HAP) were studied. These HAPs were put into organ baths and electrically stimulated (1 Hz). For comparison, we investigated isolated electrically paced (1 Hz) left atrial preparations (LA) from wild type mice (WT) or from mice with cardiac overexpression of H 2 -histamine receptors (H 2 -TG) or mice with cardiac overexpression of the human 5-HT 4 -serotonin receptors (5-HT 4 -TG). R-PIA led to negative inotropic effects (NIE) in HAP and LA from WT in the presence of isoprenaline, which were lessened by cantharidin. Likewise, R-PIA diminished force of contraction (FOC) in HAP and in LA from H 2 -TG excited by histamine, and also these NIE were made smaller by cantharidin. Similarly, R-PIA dampened FOC in HAP and in LA from 5-HT 4 -TG aroused by serotonin, and these NIE were weakened by cantharidin. We hypothesize that A 1 -adenosine receptors shrink the positive inotropic effects of β-adrenoceptors, H 2 -histamine receptors, or 5-HT 4 -serotonin receptors, in part, by activating PP1 and/or PP2A in the human atrium.

Contractile effects of dexmedetomidine in the human heart - Joachim Neumann; Uwe Kirchhefer; Britt Hofmann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Dexmedetomidine is an approved drug that is chemically related to clonidine. Dexmedetomidine is used to induce sedation and anxiolysis. These therapeutic effects of dexmedetomidine are explained by its agonistic action on brain α 2 -adrenoceptors. We tested the hypothesis that dexmedetomidine like clonidine also stimulated human cardiac atrial H 2 -histamine-receptors. We noted that 10 µM dexmedetomidine increased force of contraction in electrically stimulated (1 Hz) human right atrial preparations (HAP, obtained during open heart surgery). These effects were increased by previously applied cilostamide and slightly attenuated by subsequently applied 10 µM cimetidine but greatly attenuated by 10 µM propranolol or when first 10 µM cocaine was given. After pre-stimulation with histamine, subsequently applied 1 µM dexmedetomidine reduced force of contraction in HAP. In left atrial preparations from mice with cardiac-specific overexpression of H 2 -histamine receptors (H 2 -TG), we noted a positive inotropic effect of 10 µM dexmedetomidine in the presence of 100 nM rolipram that was reversed by cimetidine. In left atrial preparations of wild-type mice, 10 µM dexmedetomidine increased force of contraction in the presence of rolipram which was reversed by subsequently applied 10 µM propranolol and attenuated by pretreatment with 10 µM cocaine. These data indicate a direct cardiac action of dexmedetomidine. Dexmedetomidine can probably, in principle, release endogenous cardiac noradrenaline. Thus, dexmedetomidine can act as a partial agonist at human cardiac H 2 -histamine receptors but its main effect in HAP is the release of endogenous β-adrenergic catecholamines.

Tirzepatide increased force of contraction in the isolated human atrium - Joachim Neumann; Britt Hofmann; Uwe Kirchhefer; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Tirzepatide is an approved drug that is used to treat type 2 diabetes. Tirzepatide is a peptide comprised of 39 amino acids and activates glucose-dependent insulinotropic polypeptide receptors (GIPR) and glucagon-like peptide-1 receptors (GLP-1R). Via GIPR and GLP-1R, tirzepatide stimulated in cell culture adenylyl cyclases (AC) and thereby elevated the cellular content of 3′:5′ cyclic adenosine monophosphate (cAMP). We tested the hypothesis that tirzepatide augmented the force of contraction (FOC) in isolated electrically driven (1 Hz) human right atrial preparations (HAP) obtained during open heart surgery from adult patients. Cumulatively applied tirzepatide, starting at nanomolar concentrations, raised FOC in a concentration-dependent manner and a time-dependent manner ( p < 0.05). The positive inotropic effects (PIE) of tirzepatide were attenuated by about a quarter by a GIPR antagonist (100 nM, Pro3-GIP) and by about three quarters by a GLP-1R antagonist (100 nM, exendin9-39) in HAP. Tirzepatide (1 µM) was less effective than 1 µM isoprenaline in raising FOC in HAP. The inhibitor of the cAMP-dependent protein kinase called H89 reversed the PIE of tirzepatide. We suggest that tirzepatide probably acts via stimulation of GIPR and GLP-1R to exert a PIE in HAP.

Clebopride stimulates 5-HT4-serotonin receptors in the human atrium - Lina Maria Rayo Abella; Joachim Neumann; Britt Hofmann; Uwe Kirchhefer; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Clebopride resembles in its structural formula metoclopramide. Clebopride, an approved drug, is used to treat gastrointestinal diseases. Here, we tested the hypothesis that clebopride like metoclopramide acts as a partial agonist at human cardiac 5-HT 4 -serotonin-receptors. Clebopride enhanced the force of contraction (FOC) in isolated, electrically stimulated (1 Hz) left atrial preparations (LA) from transgenic mice with cardiac specific overexpression of the human 5-HT 4 -serotonin receptors (5-HT 4 -TG). Subsequently applied GR125487 (1 µM), a specific 5-HT 4 -serotonin-receptor antagonist, diminished this positive inotropic effect (PIE) of clebopride in LA from 5-HT 4 -TG. Clebopride failed to heighten FOC in LA from littermate wild-type mouse hearts (WT). Clebopride augmented the beating rate in isolated right atrial preparations (RA) from 5-HT 4 -TG but unable to do so in RA from WT. Clebopride alone (up to 10 µM) failed to augment FOC in isolated electrically stimulated (1Hz) human right atrial preparations (HAP) obtained during open heart surgery from adult patients with severe coronary heart disease. Interestingly, in the presence of the phosphodiesterase III inhibitor cilostamide, clebopride heightened FOC in HAP. GR125487 attenuated this PIE in HAP. Furthermore, when 1 µM serotonin had raised FOC in HAP, additionally applied 10 µM clebopride diminished FOC in HAP. We conclude that clebopride can act as an agonist and as an antagonist at 5-HT 4 -serotonin receptors in the human atrium.

Stimulation of histamine H1-receptors produces a positive inotropic effect in the human atrium - Thanh Hoai Pham; Lina Maria Rayo Abella; Katarina Hadova; Jan Klimas; Stefan Dhein; Steffen Pockes; Jonas Manfred Albert Schlicht; Britt Hofmann; Uwe Kirchhefer; Joachim Neumann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
There is a controversy whether histamine H 1 -receptor activation raises or lowers or does not affect contractility in the human heart. Therefore, we studied stimulation of H 1 -receptors in isolated electrically stimulated (one beat per second) human atrial preparations (HAP). For comparison, we measured force of contraction in left atrial preparations (LA) from mice with overexpression of the histamine H 1 -receptor in the heart (H 1 -TG). We detected the messenger ribonucleic acid (mRNA) expression of human histamine H 1 -receptors in HAP. In LA from H 1 -TG, each cumulatively applied concentration of histamine and a dual H 1 /H 2 -agonist called 2-(2-thiazolyl)-ethylamine (ThEA) caused a time-dependent initial negative inotropic effect followed over time by a lasting positive inotropic effect. Both effects were concentration-dependent in LA from H 1 -TG. After 100 µM cimetidine, 10 µM histamine exercised a positive inotropic effect in HAP that was diminished by 10 µM mepyramine, an H 1 -receptor antagonist. The concentrations of mepyramine and cimetidine used here are based on the work of others and our own work (e.g., Guo et al. J Cardiovasc Pharmacol. 6:1210-5 1984, Rayo Abella et al. J Pharmacol Exp Ther. 389:174-185 2024). Similarly, we observed that ThEA (10 µM, 30 µM, 100 µM cumulatively applied) induced a concentration- and time-dependent positive inotropic effect in HAP. In HAP, we detected never negative inotropic effects to either histamine or ThEA. The positive inotropic effects to ThEA in HAP were reduced by mepyramine. The positive inotropic effects of ThEA in LA from H 1 -TG and in HAP were not accompanied by reductions in the time of tension relaxation. We conclude that stimulation of histamine H 1 -receptors only increases and does not decrease force of contraction in the HAP in our patients.

Clozapine is a functional antagonist at cardiac human H2-histamine receptors - Jonas M. A. Schlicht; Undine Ahlrep; Britt Hofmann; Uwe Kirchhefer; Joachim Neumann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Clozapine is an atypical antipsychotic (neuroleptic) drug. Clozapine binds to H 2 -histamine receptors in vitro. We wanted to test the hypothesis that clozapine might be a functional antagonist at human cardiac H 2 -histamine receptors. To that end, we studied isolated electrically stimulated left atrial preparations and spontaneously beating right atrial preparations from transgenic mice with cardiomyocyte-specific overexpression of the human H 2 -histamine receptor (H 2 -TG). For comparison, we used wild-type littermate mice (WT). Finally, we measured isometric force of contraction in isolated electrically stimulated muscle strips from the human right atrium (HAP) obtained from patients during bypass surgery. After pre-stimulation with histamine, clozapine (up to 10 µM) concentration and time dependently decreased beating rate in right atrial preparations from H 2 -TG. Clozapine concentration dependently 1, 3, and 10 µM decreased histamine-stimulated force of contraction in HAP. Clozapine (10 µM) decreased also the isoprenaline-stimulated force of contraction in HAP. In summary, clozapine can antagonize the function of H 2 -histamine and β-receptors in the human heart.

Effects of congeners of amphetamine on the human heart - Joachim Neumann; Stefan Dhein; Uwe Kirchhefer; Britt Hofmann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Central stimulatory and hallucinogenic drugs of abuse like amphetamine and most congeners of amphetamine can have cardiac harmful effects. These cardiac side effects can lead to morbidities and death. In this paper, we review current knowledge on the direct and indirect effects of these amphetamine congeners on the mammalian heart—more specifically, the isolated human heart muscle preparation. In detail, we address the question of whether and how these drugs affect cardiac contractility and their mechanisms of action. Based on this information, further research areas are defined, and further research efforts are proposed.

Clonidine stimulates force of contraction via histamine H2 receptors in the human atrium - Joachim Neumann; Steffen Pockes; Laura J. Humphrys; Denise Mönnich; Lisa Forster; Uwe Kirchhefer; Britt Hofmann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Clonidine has various clinical effects mediated by agonism of α 1 - or α 2 -adrenoceptors and the blocking of hyperpolarization-activated-nucleotide-gated pacemaker channels (HCN). It is unknown whether clonidine can also stimulate human cardiac histamine H 2 receptors (hH 2 Rs). We used isolated electrically stimulated left and spontaneously beating right atrial preparations from mice overexpressing the hH 2 R specifically in the heart (H 2 -TG), and spontaneously beating right atrial preparations of guinea pigs for comparison. Moreover, we studied isolated electrically stimulated muscle strips from the human right atrium. Clonidine (1, 3, and 10 µM) increased force of contraction in isolated left atrial preparations from H 2 -TG mice. In contrast, clonidine reduced the spontaneous beating rate in right atrial preparations from H 2 -TG. Clonidine raised the beating rate in guinea pig right atrial preparations. Clonidine failed to increase the force of contraction but reduced beating rate in wild-type litter mate mice (WT). In WT, histamine failed to increase the force of contraction in left atrial preparations and beating rate in right atrial preparations. Clonidine (10 µM) increased the force of contraction in isolated human right atrial preparations. The positive inotropic effect in the human atrium was attenuated by cimetidine (10 µM). Clonidine increased the beating rate of the isolated spontaneously beating guinea pig right atrium and acted as a H 2 R partial agonist. Furthermore, clonidine showed binding to the guinea pig H 2 R (100 µM) using HEK cells in a recombinant expression system (p K i < 4.5) but hardly to the human H 2 R. These data suggest that clonidine can functionally activate cardiac human H 2 R.

Lysergic acid diethylamide stimulates cardiac human H2 histamine and cardiac human 5-HT4-serotonin receptors - Ulrich Gergs; Hannes Jacob; Pauline Braekow; Britt Hofmann; Steffen Pockes; Laura J. Humphrys; Uwe Kirchhefer; Charlotte Fehse; Joachim Neumann (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Lysergic acid diethylamide (LSD) is an artificial hallucinogenic drug. Thus, we hypothesized that LSD might act 5-HT 4 serotonin receptors and/or H 2 histamine receptors. We studied isolated electrically stimulated left atrial preparations, spontaneously beating right atrial preparations, and spontaneously beating Langendorff-perfused hearts from transgenic mice with cardiomyocyte-specific overexpression of the human 5-HT 4 receptor (5-HT 4 -TG) or of the H 2 -histamine receptor (H 2 -TG). For comparison, we used wild type littermate mice (WT). Finally, we measured isometric force of contraction in isolated electrically stimulated muscle strips from the human right atrium obtained from patients during bypass surgery. LSD (up to 10 µM) concentration dependently increased force of contraction and beating rate in left or right atrial preparations from 5-HT 4 -TG ( n = 6, p < 0.05) in 5-HT 4 -TG atrial preparations. The inotropic and chronotropic effects of LSD were antagonized by 10 µM tropisetron in 5-HT 4 -TG. In contrast, LSD (10 µM) increased force of contraction and beating rate in left or right atrial preparations, from H 2 -TG. After pre-stimulation with cilostamide (1 µM), LSD (10 µM) increased force of contraction in human atrial preparations ( n = 6, p < 0.05). The contractile effects of LSD in human atrial preparations could be antagonized by 10 µM cimetidine and 1 µM GR 125487. LSD leads to H 2 -histamine receptor and 5-HT 4 -receptor mediated cardiac effects in humans.

Ergometrine stimulates histamine H2 receptors in the isolated human atrium - Hannes Jacob; Pauline Braekow; Britt Hofmann; Uwe Kirchhefer; Lisa Forster; Denise Mönnich; Laura J. Humphrys; Steffen Pockes; Joachim Neumann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Ergometrine (6a R ,9 R )- N -(( S )-1-hydroxypropan-2-yl)-7-methyl-4,6,6a,7,8,9-hexa-hydro-indolo-[4,3- fg ]chinolin-9-carboxamide or lysergide acid β-ethanolamide or ergonovine) activates several types of serotonin and histamine receptors in the animal heart. We thus examined whether ergometrine can activate human serotonin 5-HT 4 receptors (h5-HT 4 R) and/or human histamine H 2 receptors (hH 2 R) in the heart of transgenic mice and/or in the human isolated atrium. Force of contraction or beating rates were studied in electrically stimulated left atrial or spontaneously beating right atrial preparations or spontaneously beating isolated retrogradely perfused hearts (Langendorff setup) of mice with cardiac specific overexpression of the h5-HT 4 R (5-HT 4 -TG) or of mice with cardiac specific overexpression of the hH 2 R (H 2 -TG) or in electrically stimulated human right atrial preparations obtained during cardiac surgery. Western blots to assess phospholamban (PLB) phosphorylation on serine 16 were performed. Ergometrine exerted concentration- and time-dependent positive inotropic effects and positive chronotropic effects in atrial preparations starting at 0.3 µM and reaching a plateau at 10 µM in H 2 -TGs ( n = 7). This was accompanied by an increase in PLB phosphorylation at serine 16. Ergometrine up 10 µM failed to increase force of contraction in left atrial preparations from 5-HT 4 -TGs ( n = 5). Ten micrometer ergometrine increased the force of contraction in isolated retrogradely perfused spontaneously beating heart preparations (Langendorff setup) from H 2 -TG but not 5-HT 4 -TG. In the presence of the phosphodiesterase inhibitor cilostamide (1 µM), ergometrine at 10 µM exerted positive inotropic effects in isolated electrically stimulated human right atrial preparations, obtained during cardiac surgery, and these effects were eliminated by 10 µM of the H 2 R antagonist cimetidine but not by 10 µM of the 5-HT 4 R antagonist tropisetron. Furthermore, ergometrine showed binding to human histamine H 2 receptors (at 100 µM and 1 mM) using HEK cells in a recombinant expression system (p K i < 4.5, n = 3). In conclusion, we suggest that ergometrine is an agonist at cardiac human H 2 Rs.

Temperature alters the inotropic, chronotropic and proarrhythmic effects of histamine in atrial muscle preparations from humans and H2-receptor overexpressing mice - Robert J. R. Hoffmann; Ulrich Gergs; Britt Hofmann; Uwe Kirchhefer; Joachim Neumann (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
We investigated whether hypothermia and hyperthermia can alter the efficacy and potency of histamine at increasing the force of cardiac contractions in mice that overexpress the human H 2 receptor only in their cardiac myocytes (labelled H 2 -TG). Contractile studies were performed in an organ bath on isolated, electrically driven (1 Hz) left atrial preparations and spontaneously beating right atrial preparations from H 2 -TG mice and wild-type (WT) littermate control mice. The basal beating rate in the right atrial preparations from H 2 -TG mice was lowered by hypothermia (23 °C) and elevated by hyperthermia (42 °C). Furthermore, the efficacy of histamine (0.01–100 µM) at exerting positive inotropic effects was more severely attenuated in the left and right H 2 -TG mouse atria under hypothermia and hyperthermia than under normothermia (37 °C). Similarly, the inotropic response to histamine was attenuated under hypothermia and hyperthermia in isolated electrically stimulated (1 Hz) right atrial preparations obtained from humans undergoing cardiac surgery. The phosphorylation state of phospholamban at serine 16 at 23 °C was inferior to that at 37 °C in left atrial preparations from H 2 -TG mice in the presence of 10 µM histamine. In contrast, in human atrial preparations, the phosphorylation state of phospholamban at serine 16 in the presence of 100 µM histamine was lower at 42 °C than at 37 °C. Finally, under hyperthermia, we recorded more and longer lasting arrhythmias in right atrial preparations from H 2 -TG mice than in those from WT mice. We conclude that the inotropic effects of histamine in H 2 -TG mice and in human atrial preparations, as well as the chronotropic effects of histamine in H 2 -TG mice, are temperature dependent. Furthermore, we observed that, even without stimulation of the H 2 receptors by exogenous agonists, temperature elevation can increase arrhythmias in isolated right atrial preparations from H 2 -TG mice. We propose that H 2 receptors play a role in hyperthermia-induced supraventricular arrhythmias in human patients.

Correction to: Functional interaction of H2‑receptors and 5-HT4‑receptors in atrial tissues isolated from double transgenic mice and from human patients - Joachim Neumann; Denise Schwarzer; Charlotte Fehse; Rebecca Schwarz; Margareta Marusakova; Uwe Kirchhefer; Britt Hofmann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Functional interaction of H2-receptors and 5HT4-receptors in atrial tissues isolated from double transgenic mice and from human patients - Joachim Neumann; Denise Schwarzer; Charlotte Fehse; Rebecca Schwarz; Margareta Marusakova; Uwe Kirchhefer; Britt Hofmann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)
In the past, we generated transgenic mice that overexpress the human histamine 2 (H 2 )-receptor (H 2 -TG) or that overexpress the human serotonin 4 (5-HT 4 )-receptor (5-HT 4 -TG) in the heart. Here, we crossbred these lines of mice to generate double transgenic mice that overexpress both receptors (DT). This was done to study a conceivable interaction between these receptors in the mouse heart as a model for the human heart. When in left atria, initially, force of contraction was elevated maximally with 1 µM serotonin, and subsequently, histamine was cumulatively applied; a biphasic effect of histamine was noted: the force of contraction initially decreased, maximally at 10 nM histamine, and thereafter, the force of contraction increased again at 1 µM histamine. Notably, functional interaction between 5-HT and histamine was also identified in isolated electrically stimulated trabeculae carneae from human right atrium (obtained during cardiac surgery). These functional and biochemical data together are consistent with a joint overexpression of inotropically active H 2 -receptors and 5-HT 4 -receptors in the same mouse heart. We also describe an antagonistic interaction on the force of contraction of both receptors in the mouse atrium (DT) and in the human atrial muscle strips. We speculate that via this interaction, histamine might act as a “brake” on the cardiac actions of 5-HT via inhibitory GTP-binding proteins acting on the activity of adenylyl cyclase.

Amitriptyline functionally antagonizes cardiac H2 histamine receptors in transgenic mice and human atria - Joachim Neumann; Maximilian Benedikt Binter; Charlotte Fehse; Margaréta Marušáková; Maren Luise Büxel; Uwe Kirchhefer; Britt Hofmann; Ulrich Gergs (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)
We have previously shown that histamine (2-(1 H -imidazol-4-yl)ethanamine) exerted concentration-dependent positive inotropic effects (PIE) or positive chronotropic effects (PCE) on isolated left and right atria, respectively, of transgenic (H 2 R-TG) mice that overexpress the human H 2 histamine receptor (H 2 R) in the heart; however, the effects were not seen in their wild-type (WT) littermates. Amitriptyline, which is still a highly prescribed antidepressant drug, was reported to act as antagonist on H 2 Rs. Here, we wanted to determine whether the histamine effects in H 2 R-TG were antagonized by amitriptyline. Contractile studies were performed on isolated left and right atrial preparations, isolated perfused hearts from H 2 R-TG and WT mice and human atrial preparations. Amitriptyline shifted the concentration-dependent PIE of histamine (1 nM–10 μM) to higher concentrations (rightward shift) in left atrial preparations from H 2 R-TG. Similarly, in isolated perfused hearts from H 2 R-TG and WT mice, histamine increased the contractile parameters and the phosphorylation state of phospholamban (PLB) at serine 16 in the H 2 R-TG mice, but not in the WT mice. However, the increases in contractility and PLB phosphorylation were attenuated by the addition of amitriptyline in perfused hearts from H 2 R-TG. In isolated electrically stimulated human atria, the PIE of histamine that was applied in increasing concentrations from 1 nM to 10 μM was reduced by 10-μM amitriptyline. In summary, we present functional evidence that amitriptyline also acts as an antagonist of contractility at H 2 Rs in H 2 R-TG mouse hearts and in the human heart which might in part explain the side effects of amitriptyline.

Successful overexpression of wild-type inhibitor-2 of PP1 in cardiovascular cells - Thorsten Krause; Stefanie Grote-Wessels; Felix Balzer; Peter Boknik; Ulrich Gergs; Uwe Kirchhefer; Igor B. Buchwalow; Frank U. Müller; Wilhelm Schmitz; Joachim Neumann (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Rezensionen - Joachim Neumann; Uwe Schwarz (KN - Journal of Cartography and Geographic Information, 2018)

Native plasmids restrict growth of Phaeobacter inhibens DSM 17395: Energetic costs of plasmids assessed by quantitative physiological analyses - Kathleen Trautwein; Sabine Eva Will; Reiner Hulsch; Uwe Maschmann; Katharina Wiegmann; Michael Hensler; Victoria Michael; Hanna Ruppersberg; Daniel Wünsch; Christoph Feenders; Meina Neumann‐Schaal; Sabine Kaltenhäuser; et al. (Environmental Microbiology, 2016)
Summary Plasmid carriage is associated with energetic costs, and thus only those plasmids providing fitness benefits are stably maintained in the host lineage. Marine bacteria of the Roseobacter clade harbor up to 11 extrachromosomal replicons, adding lifestyle‐relevant and possibly habitat success‐promoting functions to their genomic repertoire. Phaeobacter inhibens DSM 17395 is a nutritionally versatile representative, carrying three stable and functionally distinct plasmids (65, 78, and 262 kb). The present study investigates the physiological and energetic consequences of plasmid carriage in P. inhibens DSM 17395, employing mutants cured from all native plasmids in every possible combination (seven different). Cultivation in process‐controlled bioreactors with casamino acids as organic substrate revealed a complex physiological response, suggesting existence of functional interconnections between the replicons. Deletion of the 262 kb plasmid boosted growth rate (>3‐fold) and growth efficiency (yields for carbon, O 2 and CO 2 ), which was not observed for the 65 or 78 kb plasmid. Carriage of the 262 kb plasmid was most costly for the wild type, i.e. contributing ∼50% to its energetic (dissimilatory) expenditures. Cost–benefit analysis of plasmid carriage reflects the high value of plasmids for niche specialization of P. inhibens DSM 17395 and most likely also for related Phaeobacter species.

In-Lake Neutralization: Quantification and Prognoses of the Acid Load into a Conditioned Pit Lake (Lake Bockwitz, Central Germany) - Kai-Uwe Ulrich; Christian Bethge; Ina Guderitz; Ben Heinrich; Volker Neumann; Claus Nitsche; Friedrich-Carl Benthaus (Mine Water and the Environment, 2012)

Protein phosphatase 2A affects myofilament contractility in non-failing but not in failing human myocardium - Paul J. M. Wijnker; Peter Boknik; Ulrich Gergs; Frank U. Müller; Joachim Neumann; Cris dos Remedios; Wilhelm Schmitz; Jürgen R. Sindermann; Ger J. M. Stienen; Jolanda van der Velden; Uwe Kirchhefer (Journal of Muscle Research and Cell Motility, 2011)

Return of twaite shad Alosa fallax (Lacépède, 1803) to the Southern Baltic Sea and the transitional area between the Baltic and North Seas - Ralf Thiel; Philip Riel; Renate Neumann; Helmut M. Winkler; Uwe Böttcher; Tomas Gröhsler (Hydrobiologia, 2008)

Purification and characterisation of a jacalin-related, coleoptile specific lectin from Hordeum vulgare - Ingo Grunwald; Ines Heinig; Hubert H. Thole; Dieter Neumann; Uwe Kahmann; Klaus Kloppstech; Achim E. Gau (Planta, 2007)

Cells of Pseudomonas putida and Enterobacter sp. adapt to toxic organic compounds by increasing their size - Grit Neumann; Y. Veeranagouda; T. B. Karegoudar; zlem Sahin; Ines Musezahl; Nadja Kabelitz; Uwe Kappelmeyer; Hermann J. Heipieper (Extremophiles, 2005)

Characterization of Porin from Roseobacter denitrificans - Uwe Neumann; Elke Maier; Emile Schiltz; Jürgen Weckesser; Roland Benz (Antonie van Leeuwenhoek, 1997)